Enrollment and Eligibility Process of Brazil’s Auxílio Emergencial : Data Processing and Use of Administrative Registries - World Bank (Washington, DC, 2022)
In order to support the systematization of institutional learning processes provided by the implementation of Auxílio Emergencial in Brazil and disseminate the best practices derived from the Brazilian experience to social policy operators and administrators in other developing countries, the World Bank headed up a study on the social protection response to the Covid-19 pandemic in Brazil. Financed by the Foreign, Commonwealth & Development Office (FCDO), which is linked to the Foreign Secretary of the Government of the United Kingdom, this study was conducted at the request and with the cooperation of the Brazilian Government. This project encompasses the preparation of a main Report covering the stages of the Auxílio Emergencial, together with four Technical Notes exploring specific implementation aspects in greater depth. One of them addresses registration and eligibility verification strategies, which form the subject of this text.